Pengaruh Gaya Hidup Berbelanja, Electronic Word of Mouth dan Flash Sale Terhadap Pembelian Impulsif Pada Social Commerce Tiktok Shop (Studi Kasus Pada Mahasiswa Pengguna Tiktok Shop di Kota Malang) - Ade Kafa Bih; Agus Widarko; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Impulsive Buying is a consumer buying behavior that does not plan to purchase a product in advance. The purpose of this study is to determine the influence of shopping lifestyle, electronic word of mouth, and flash sale on impulsive purchases on tiktok shop social commerce. This research was conducted on students who use Tiktok Shop in Malang City, using a quantitative approach. The sampling technique uses a non-probability sampling method with purposive sampling technique. Determination of the number of samples using the lemeshow formula which amounted to 96 respondents. The data analysis methods used are instrument tests, normality tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The results showed that simultaneously the lifestyle of shopping, electronic word of mouth, and flash sale had a significant effect on impulsive purchases on tiktok shop social commerce. The lifestyle of shopping and flash sales partially has a significant effect on impulsive purchases on social commerce Tiktok Shop, while electronic word of mouth does not have a significant effect on impulsive purchases on social commerce Tiktok Shop. The influence of shopping lifestyle, electronic word of mouth, and flash sale on impulsive purchases shows a coefficient of determination of 36.6%. Keywords: Shopping Lifestyle, Electronic Word of Mouth, Flash Sale, And Impulsive Buying.